Amelioration of Altered Blood Glucose Level by Improving Acetate and Serotonin Level of Brain in Immobilized Stressed Rat - Mohale, Deepak Suresh (International Journal of Pharmaceutical & Biological Archive, 2023)
Objective: The present study was designed to determine the effect of acetate and selective serotonin reuptake inhibitors (SSRI) on stress and blood glucose levels in stressed rats. Materials and Methods: Animals were divided into five groups (n = 6), treated with 20 mg/kg p.o. of fluoxetine (SSRI) and glyceryl triacetate (GTA) at 6 g/kg p.o. dose (acetate supplementation) alone and in combination. For 28 days to assess its effect in immobilized stressed rats. Open field and hole board tests were used for the determination of stress in animals, followed by blood glucose levels. Results: Animals treated with 20 mg/kg p.o. fluoxetine (SSRI), 6 g/kg p.o GTA, and SSRI (fluoxetine) + GTA showed significant (P < 0.01) stress-resistant activity as compared to negative control. Results also demonstrated that there was a significant (P < 0.01) decrease in blood glucose levels in animals treated with 20 mg/kg p.o. fluoxetine (SSRI), 6 g/kg p.o. GTA, and SSRI (fluoxetine) + GTA. Conclusion: The present study concludes that acetate and SSRI supplementation possess stress-resistant and hypoglycemic potential in immobilized stressed rats by enhancing the acetylation of histone.